Perlindungan Hukum Terhadap Dokter Dalam Pelayanan BPJS Perspektif Hukum Pidana Dan Etik Kedokteran - Gutimigo, Zelta Pratiwi; Fakih, M; Triono, Agus; Maroni, Maroni; Firmansyah, Ade Arif; Muhtadi, Muhtadi (VIVA THEMIS, 2025)
The National Health Insurance Program (JKN) by BPJS Kesehatan provides broad access to health services to the public, but also presents its own challenges for doctors in carrying out their professional duties. The high workload, limited facilities, and patient expectations can pose a risk of criminalization for medical actions, even though they are in accordance with professional standards. This study aims to examine the forms and limits of criminal liability of doctors in BPJS services based on positive law in Indonesia, as well as examine how the principles of medical ethics become the basis of legal protection for doctors. The method used is a normative juridical approach with a literature study of relevant laws and regulations, such as Law Number 17 of 2023 concerning Health, Criminal Code, Presidential Regulation Number 59 of 2024 as an amendment to Presidential Regulation Number 82 of 2018 concerning Health Insurance, and other professional regulations. The results showed that doctors in the JKN system by BPJS have limited criminal liability, as long as medical actions are carried out according to professional standards and operational procedures. Medical ethical principles such as beneficence, non-maleficence, autonomy, and justice provide an important basis for legal protection, especially when doctors face a dilemma between professional obligations and system restrictions. Integration between law, ethics, and policy is needed to ensure fair legal protection for doctors in the practice of national health services